Global changes in extreme tropical cyclone wave heights under projected future climate conditions - Guisela Grossmann-Matheson; Ian R. Young; Alberto Meucci; Jose-Henrique Alves (Scientific Reports)
Abstract Tropical cyclone risks are expected to increase with climate change. One such risk is extreme ocean waves generated by surface winds from these systems. We use synthetic databases of both historical (1980-2017) and future (2015-2050) tropical cyclone tracks to generate wind fields and force a computationally efficient wave model to estimate significant wave heights across all global tropical cyclone basins. These data are then used to estimate 1 in 100-year return period significant wave height for both the historical period and the future under an SSP585 high emissions scenario. The results show that by 2050, there are projected increases in 100-year significant wave height of up to 1.5 m (10%) in the Eastern and Western Pacific, South Indian and South Pacific Ocean basins. The North Atlantic basin shows no consistent trend, whilst the North Indian basin (particularly the Bay of Bengal) shows a statistically significant decrease in extreme significant wave height. The results represent the first attempt to quantify the magnitude of expected changes in extreme wave height conditions generated by extreme tropical cyclones across all tropical cyclone basins.